Rare, "Red Book" species of plants and animals in Baikal Siberia under CITES protection (in the context of sustainable development) - E. N. Yelaev; A. A. Alekseeva; A. A. Mokrov; N. G. Yelaeva (Юг России: экология, развитие)
Aim. To carry out an ongoing assessment of the status of rare and endangered species of plants and animals listed in the applicable Red Books and subject to the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), which are of particular value for the conservation of biological diversity in the interests of sustainable development of Baikal Siberia and to identify problems with the use of some species in the region.The material for the review were the regional Red Books published in recent years (from 2012 to 2023) in all regions of the Russian Federation included in Baikal Siberia (Buryat Republic, Transbaikalian Region, Irkutsk Region), as well as the Red Book of the Russian Federation (2021) and the list of species from the Annexes of the CITES Convention.An updated list of rare, "Red Book" species of animals and plants of Baikal Siberia, subject to the CITES Convention, is presented. The categories of rare, endangered, and environmental protection statuses in all regional Red Books of Baikal Siberia are aligned with the accepted statuses in the Red Book of the Russian Federation, which currently meets international standards. In the 2nd edition of the Russian Federation Red Book (2021), 213 species of animals fall under the CITES Convention, 164 species of plants. In the Buryat Republic, the Transbaikalian Region and the Irkutsk Oblast Red Books (2012, 2020, 2021, 2023) 35 species of plants and 40 species of animals are from the CITES List. Annex I includes all endangered species whose trade is strictly regulated and should be allowed only in exceptional cases (amounting to a total of 13 species, whose trade has or may have an impact on their continued existence). In Annex II, which includes all species that may be threatened with extinction if the trade in specimens of such species is not strictly regulated (31 plant species and 57 animal species). Although they are not necessarily in immediate danger of extinction at this time, they may become so, if the trade in specimens of such species is not strictly regulated in order to prevent  use incompatible with their survival. There are no protected species in the region from Annex III.An audit of the most vulnerable rare and Red Book species of plants and animals was carried out, as well as of the validity of including certain species in the Red Books (federal and regional) and the CITES List for the Biological Diversity Conservation and Sustainable Development of Baikal Siberia.